Nitrogen-doped multi-carbon-based composite conductive paste, negative electrode sheet and secondary battery
By using nitrogen-doped multi-carbon-based composite conductive paste, the problems of poor conductivity and large volume changes of silicon-based anode materials are solved, and its electrochemical performance and cyclic stability are significantly improved.
Patent Information
- Application Number
- CN202211637448.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-15
AI Technical Summary
In the prior art, the silicon-based negative electrode material has poor conductivity and large volume changes, resulting in short cycle life, low first-time efficiency, and small reversible capacity, which limits its practical application.
Using nitrogen-doped multi-carbon-based composite conductive paste, a carbon-based precursor, porous carbon and composite paste are prepared to form a composite material with high conductivity, which is used to improve the electrochemical performance of the silicon-based negative electrode.
It significantly improves the conductivity and cycle stability of the silicon-based negative electrode, extends the cycle life of the battery, and improves the electrochemical performance.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, in particular to a conductive agent, and more particularly to a nitrogen-doped multi-carbon-based composite conductive slurry, a negative electrode sheet and a secondary battery. Background Art
[0002] In the current situation, lithium-ion batteries are the main power source for electric and hybrid vehicles. However, graphite anodes cannot meet the high energy requirements of future automotive technology due to their limited specific capacity (372 mAh / g). Si is one of the most promising anode active materials because of its high theoretical capacity (4200 mAh / g), low working potential (0.35 V vs Li / Li+), and natural abundance. However, Si has a large volume change during charge and discharge, resulting in short cycle life, low first efficiency, and small reversible capacity, which limits the practical use of Si anodes. Silicon has poor conductivity (~10 -5 S / cm, much lower than carbon and graphite (10-10 4 S / cm), is another problem that needs to be overcome in the application of silicon anode. The large number of boundaries in the nanostructured Si anode further hinders the electron transport. Therefore, it is crucial to build a strong conductive network in the Si anode to maintain the electron pathway and reduce the battery impedance.
[0003] There have been many studies on the application of conductive additives in various positive electrode materials and graphite negative electrode materials, and the results have been proven to be significant. However, there are not many reports on the application of suitable conductive agents in Si-based negative electrodes. The mainstream conductive agent on the market is currently low-cost nano-scale conductive carbon black. However, zero-dimensional carbon black particles tend to aggregate with each other. Therefore, it is difficult to form a continuous conductive network that fully utilizes all active substances. Especially when working with silicon-based negative electrodes, the electrical disconnection of Si, solid electrolyte and conductive agent particles under severe expansion and contraction can lead to battery failure.
[0004] To solve this problem, the industry has used one-dimensional carbon nanotubes, two-dimensional graphene or three-dimensional carbon coatings to modify Si particles to make Si composite negative electrode materials. However, the carbon matrix in this material not only constructs a layered 3D conductive network, but also needs to act as a structural buffer to prevent large volume changes of silicon to improve the electrochemical performance of the material, including cycle stability. However, the production cost of commercially available carbon nanotubes and graphene is relatively high, and the cost of modifying Si particles is relatively high. Therefore, it is necessary to develop suitable conductive agents to reduce costs while meeting the needs of improving the electrochemical performance of silicon-based negative electrodes, including cycle stability. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a nitrogen-doped multi-carbon-based composite conductive paste, a negative electrode sheet and a secondary battery. The obtained nitrogen-doped multi-carbon-based composite conductive paste has a lower resistivity and is used in a silicon-based negative electrode to greatly improve the electrochemical performance of the silicon-based negative electrode.
[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, comprising the steps of:
[0007] (I) Preparation of carbon-based precursors
[0008] The carbon material, the activator, the nitrogen source and the nano-alumina are ground and mixed, and carbonized under an inert atmosphere to obtain a carbon-based precursor, wherein the activator is a particle having oxygen-containing groups on the surface;
[0009] (II) Preparation of porous carbon
[0010] The carbon-based precursor is acid-washed and then post-treated to obtain porous carbon;
[0011] (III) Preparation of composite slurry
[0012] The porous carbon and the carbon-based conductive auxiliary material are added into the dispersion to obtain a pre-dispersion solution, and the pre-dispersion solution is stripped and ground.
[0013] The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste of the present invention at least includes the following technical effects.
[0014] (1) The present invention uses particles with oxygen-containing groups on the surface as activators. The oxygen-containing groups can activate carbon materials. The porous carbon surface generated after carbonization and acid washing has many defects, which is beneficial to improving the conductivity of the material.
[0015] (2) After acid washing, the carbon-based precursor can remove the nano-alumina to obtain porous carbon. When preparing the negative electrode slurry, the three-dimensional porous carbon increases the chance of electrical contact with Si particles, thereby generating new conductive paths. Secondly, after the porous carbon and the carbon-based conductive auxiliary material are compounded, they have higher conductivity, which can effectively separate Si particles from each other, thereby inhibiting their aggregation, and prevent the internal silicon from being unable to participate in charging and discharging when the aggregates become too large, thereby improving the electrochemical performance of the silicon-based negative electrode.
[0016] (3) Nitrogen source doping can significantly change the elemental composition of the porous carbon surface, manipulate its surface activity, and improve the electrochemical properties of porous carbon. Because nitrogen atoms have one more extranuclear electron than carbon atoms and have a high electron affinity, the carbon atoms adjacent to N atoms in nitrogen-doped carbon materials have a high positive charge density. At the same time, there is a conjugated effect between the lone pair of electrons of the N atom and the large π bond of the carbon atom lattice, which makes the nitrogen-doped carbon material exhibit excellent electrochemical properties.
[0017] In some embodiments, the carbon-based material includes at least one of solid phase pitch, liquid phase pitch, coal tar, resin, and aromatic oil.
[0018] In some embodiments, the carbon-based material has a coking value of 10% to 80%.
[0019] In some embodiments, the nitrogen source is at least one of melamine, urea, dopamine, and pyridine.
[0020] In some embodiments, the activator is at least one of potassium hydroxide, sodium hydroxide, calcium carbonate, and magnesium oxide.
[0021] In some embodiments, the mass ratio of the carbon material, the activator, the nitrogen source and the nano-alumina is 14.0-62.0:11.5-32.5:0.5-10.0:5.0-10.0.
[0022] In some embodiments, the equipment used for grinding in the preparation of the carbon-based precursor in step (I) is a ball mill, and the ball milling time is 8 hours to 20 hours.
[0023] In some embodiments, the equipment used for mixing in the preparation of the carbon-based precursor in step (I) is a fusion machine or a VC mixer, and the mixing time is 60 min to 180 min.
[0024] In some embodiments, the flow rate of the inert atmosphere is 0.5 L / min to 20.0 L / min.
[0025] In some embodiments, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0026] In some embodiments, the equipment used for carbonization is a roller kiln, a rotary kiln, a box furnace or a vertical kettle.
[0027] In some embodiments, the solution used for pickling is hydrochloric acid, nitric acid, or hydrofluoric acid.
[0028] In some embodiments, the carbon-based conductive auxiliary material includes at least one of graphene quantum dots, conductive carbon black, and single-walled carbon nanotubes.
[0029] In some embodiments, the stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 250 bar to 4000 bar.
[0030] In some embodiments, the grinding in the step (III) of preparing the composite slurry is performed by mechanical grinding, and the mechanical grinding is performed by high-speed shearing method to grind the particle size to less than 10 μm.
[0031] In some embodiments, the pre-dispersion is mechanically ground prior to exfoliation.
[0032] In some embodiments, the carbonization temperature is increased in a gradient manner, and the maximum temperature is increased to 800°C to 900°C.
[0033] In some embodiments, the heating rate of carbonization is 1° C. / min to 5° C. / min.
[0034] In some embodiments, the carbonization temperature is first increased to 250° C. to 300° C., then to 300° C. to 480° C., and then to 480° C. to 850° C., and then maintained for 120 min to 300 min.
[0035] In some embodiments, the post-treatment includes sequentially washing, filtering, drying, grinding, and sieving the acid-washed carbon-based precursor.
[0036] In some embodiments, the pre-dispersion includes 10 wt.% to 25 wt.% of porous carbon, 0.01 wt.% to 2 wt.% of a carbon-based conductive auxiliary material, 5 wt.% to 10 wt.% of a dispersant, and 70 wt.% to 90 wt.% of a solvent.
[0037] In some embodiments, the carbon-based conductive auxiliary material includes at least one of graphene quantum dots, conductive carbon black, and single-walled carbon nanotubes.
[0038] In some embodiments, the carbon-based conductive auxiliary material includes at least single-walled carbon nanotubes, and the diameter of the single-walled carbon nanotubes is 0.2 nm to 4 nm.
[0039] In some embodiments, the dispersant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate, polyethylene oxide, polyether having multiple anchoring groups, polyethylene glycol and acrylonitrile multipolymer.
[0040] In some embodiments, the solvent is at least one of N,N-dimethylformamide, methanol, ethanol, ethylene glycol, ethyl acetate, acetone, and deionized water.
[0041] To achieve the above-mentioned purpose, the second aspect of the present invention provides a negative electrode sheet, including a negative electrode active material, a conductive agent and a binder, the negative electrode active material includes at least a silicon-based material, and the conductive agent includes a nitrogen-doped multi-carbon-based composite conductive paste prepared by the aforementioned method for preparing a nitrogen-doped multi-carbon-based composite conductive paste.
[0042] To achieve the above-mentioned objectives, the third aspect of the present invention provides a secondary battery, comprising a positive electrode and a negative electrode, the positive electrode comprising a positive electrode conductive agent, the negative electrode comprising a negative electrode conductive agent, and at least one of the positive electrode conductive agent and the negative electrode conductive agent comprises a nitrogen-doped multi-carbon-based composite conductive paste prepared by the aforementioned method for preparing the nitrogen-doped multi-carbon-based composite conductive paste. DETAILED DESCRIPTION
[0043] The nitrogen-doped multi-carbon-based composite conductive paste prepared by the preparation method of the present invention can be used as a positive electrode or negative electrode conductive agent in a secondary battery. The secondary battery includes a positive electrode material and a negative electrode material.
[0044] The positive electrode material includes a positive electrode active material, a conductive agent and a binder. The mass ratio of the positive electrode active material, the binder and the conductive agent may be 80-99:0.5-20:0.5-20. The positive electrode active material includes at least one of a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material, a nickel cobalt manganese oxide positive electrode material and a nickel cobalt aluminum oxide positive electrode material. The binder may be, for example but not limited to, at least one of polyoxyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl pyrrolidone, styrene-butadiene rubber, acrylated styrene-butadiene rubber and epoxy resin. The positive electrode current collector may be aluminum foil. The solvent of the positive electrode slurry may be N-methylpyrrolidone or N-vinylpyrrolidone. The conductive agent is used to improve the conductivity of the positive electrode. The conductive agent may include the nitrogen-doped multi-carbon-based composite conductive paste of the present invention, or include carbon-containing materials such as carbon black, acetylene black, Ketjen black, carbon fiber, or metal powders or metal fiber materials such as copper, nickel, aluminum, silver, or conductive polymers such as polyphenylene derivatives, or mixtures thereof.
[0045] The negative electrode material includes a negative electrode active material, a conductive agent and a binder. The mass ratio of the negative electrode active material, the binder and the conductive agent can be 60-99:0.1-20:0.1-20. The negative electrode material at least includes a silicon-based negative electrode material, and may further include a graphite material, soft carbon or hard carbon. The silicon-based negative electrode material can be, but is not limited to, SiO x or carbon-coated SiO x , 0≤x<2. The binder is used to improve the bonding between the negative electrode material particles and between the negative electrode material particles and the negative electrode current collector. The binder is selected from at least one of polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, styrene-butadiene rubber and acrylated styrene-butadiene rubber. The conductive agent at least includes the nitrogen-doped multi-carbon-based composite conductive slurry of the present invention, and may further include carbon black, acetylene black, Ketjen black, carbon fiber and other carbon-containing materials, or metal powders or metal fiber materials such as copper, nickel, aluminum, silver, etc., or conductive polymers such as polyphenylene derivatives, or mixtures thereof.
[0046] The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste of the present invention comprises step (I) preparing a carbon-based precursor, step (II) preparing porous carbon and step (III) preparing a composite paste.
[0047] Among them, step (I) of preparing the carbon-based precursor includes grinding and mixing the carbon material, the activator, the nitrogen source and the nano-alumina, and carbonizing them under an inert atmosphere to obtain the carbon-based precursor, and the activator is a particle having oxygen-containing groups on the surface.
[0048] As an embodiment, the mass ratio of carbon material, activator, nitrogen source and nano alumina is 14.0-62.0:11.5-32.5:0.5-10.0:5.0-10.0. As an example, the mass ratio of the four can be, but is not limited to, 14.2:15.2:0.5:5.0, 20:16:5:5, 22:30:10:6, 23:25:5:7, 35:20:5:7, 45:20:10:5, 55:30:1:6, 62:25:5:6, 45:25:5:6, 30:20:5:6, 30:30:10:10, 55: 20:6:8, 40:18:10:10, 55:30:10:9, 25:20:1:9, 35:20:5:9, 45:20:4:9, 55:29:6:9, 60:20:9:9, 35:20:8:9, 35:15:5:9, 35:30:7:10, 45:30:5:10, 40:18:6:10, 60:30:5:10.
[0049] As an embodiment, the carbon material includes at least one of solid phase asphalt, liquid phase asphalt, coal tar, resin and aromatic oil. The coking value of the carbon material is 10% to 80%, as some embodiments, the coking value is 30% to 80%, as some embodiments, the coking value is 50% to 80%. The coking value can be specifically but not limited to 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%.
[0050] As one embodiment, the nitrogen source is at least one of melamine, urea, dopamine and pyridine. Such nitrogen-containing substances can form a three-dimensional network structure before carbonization. After sintering, nitrogen atoms are combined in a complex mesh structure, which can improve the conductivity of the material.
[0051] As an embodiment, the activator is at least one of potassium hydroxide, sodium hydroxide, calcium carbonate and magnesium oxide, and as an example, the activator is potassium hydroxide. During the preparation process of such substances, the particles inevitably have surface groups, such as phenolic groups, ether groups, carbonyl groups and other oxygen-containing groups, and some contain some acidic groups, so they can be used as activators to provide oxygen components to help activate carbon materials.
[0052] As one embodiment, the equipment used for grinding in preparing the carbon-based precursor in step (I) is a ball mill, and the ball milling time is 8 to 20 hours, specifically but not limited to 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours.
[0053] As an embodiment, the equipment used for mixing in the preparation of the carbon-based precursor in step (I) is a fusion machine or a VC mixer, and the fusion machine can be a room temperature fusion machine or a heated fusion machine, including but not limited to a VC mixer. The mixing time is 60 min to 180 min, specifically but not limited to 60 min, 70 min, 90 min, 110 min, 130 min, 150 min, 170 min, 180 min.
[0054] As one embodiment, the inert atmosphere includes at least one of nitrogen, argon and helium. The flow rate of the inert atmosphere is 0.5 L / min to 20.0 L / min, specifically but not limited to 0.5 L / min, 1.5 L / min, 2.5 L / min, 3.5 L / min, 4.5 L / min, 5.5 L / min, 6.5 L / min, 7.5 L / min, 8.5 L / min, 9.5 L / min, 11.0 L / min, 13.0 L / min, 15.0 L / min, 17.0 L / min, 19.0 L / min, 20.0 L / min.
[0055] As an embodiment, the equipment used for carbonization is a roller kiln, a rotary kiln, a box furnace or a vertical kettle. As an example, the equipment used for carbonization is a roller kiln.
[0056] As an embodiment, the temperature of carbonization is increased in a gradient manner, and the maximum temperature is increased to 800° C. to 900° C., and the maximum temperature may be, but is not limited to, 800° C., 820° C., 840° C., 860° C., 880° C., and 900° C. The temperature increase rate of carbonization is 1° C. / min to 5° C. / min, and the temperature increase rate may be, but is not limited to, 1° C. / min, 2° C. / min, 3° C. / min, 4° C. / min, and 5° C. / min. The carbonization temperature can be increased in four gradients. As an example, the carbonization temperature is first increased to 250°C to 300°C, and then increased to 300°C to 480°C and 480°C to 850°C in sequence, and then kept warm for 120min to 300min, specifically but not limited to 120min, 130min, 150min, 170min, 190min, 210min, 230min, 250min, 270min, 290min and 300min.
[0057] Step (II) of preparing porous carbon includes acid washing the carbon-based precursor and then post-treating it to obtain porous carbon.
[0058] As an embodiment, the solution used for pickling is hydrochloric acid, nitric acid or hydrofluoric acid, or a dilute solution of hydrochloric acid, nitric acid or hydrofluoric acid, and the pickling is performed to remove residual ions.
[0059] As an embodiment, the post-treatment includes washing, filtering, drying, grinding and sieving the acid-washed carbon-based precursor in sequence. Acidification and water washing can be repeatedly cycled 10 times to remove aluminum oxide and surface impurities to form porous carbon. Filtration includes suction filtration, centrifugation or filter pressing. The equipment used for drying is an oven or a dryer, and the temperature used for drying is 80°C to 160°C. The drying temperature may be, but is not limited to, 80°C, 100°C, 120°C, 140°C, and 160°C. The drying time is 1h to 36h, and the drying time may be, but is not limited to, 1h, 5h, 10h, 15h, 20h, 25h, 30h, and 36h. The equipment used for grinding is a ball mill, and the ball milling time is 10h to 20h, and may be, but is not limited to, 10h, 11h, 13h, 15h, 17h, 19h, and 20h. Screening can pass through a 200 to 400 mesh sieve.
[0060] Step (III) of preparing the composite slurry comprises adding porous carbon and carbon-based conductive auxiliary materials into the dispersion to obtain a pre-dispersion liquid, and then stripping and grinding the pre-dispersion liquid.
[0061] As one embodiment, the pre-dispersion liquid includes 10 wt.% to 25 wt.% of porous carbon, 0.01 wt.% to 2 wt.% of carbon-based conductive auxiliary material, 5 wt.% to 10 wt.% of dispersant and 70 wt.% to 90 wt.% of solvent.
[0062] As one embodiment, the content of porous carbon may be, but is not limited to, 10 wt.%, 12 wt.%, 14 wt.%, 16 wt.%, 18 wt.%, 20 wt.%, 22 wt.%, 24 wt.%, or 25 wt.%.
[0063] As an embodiment, the content of the carbon-based conductive auxiliary material can be, but is not limited to, 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1.0wt.%, 1.2wt.%, 1.4wt.%, 1.6wt.%, 1.8wt.%, 2wt.%. As an embodiment, the carbon-based conductive auxiliary material includes at least one of graphene quantum dots, conductive carbon black and single-walled carbon nanotubes. As an example, the carbon-based conductive auxiliary material includes graphene quantum dots, conductive carbon black and single-walled carbon nanotubes, and the weight ratio of the three in the pre-dispersion liquid is independently 0.01wt.% to 0.5wt.%. As an example, the weight ratio of the three in the pre-dispersion liquid can be independently but not limited to 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%. Through zero-dimensional conductive carbon black, graphene quantum dots can be evenly dispersed in the three-dimensional porous carbon network, which can reduce its internal agglomeration. In addition, when a small amount of carbon nanotubes are dispersed in the porous carbon matrix, not only the fatal shortcomings of low solid content and high cost of oily pure carbon nanotube conductive slurry are avoided, but also the shortcomings of difficult dispersion of carbon nanotube conductive slurry are avoided. A small amount of carbon nanotubes has high conductivity and large aspect ratio, which can improve the electron transmission capacity of electrode materials. The hollow structure is conducive to absorbing more electrolyte, increasing the migration rate of lithium ions in the electrolyte, and improving the conductive performance of the conductive slurry to a certain extent. On the basis of porous carbon, the coordinated conductive carbon black, carbon nanotubes, etc. can greatly improve the rate performance and cycle performance of silicon negative electrode materials. As an embodiment, the carbon-based conductive auxiliary material includes at least single-walled carbon nanotubes, and the diameter of the single-walled carbon nanotubes is 0.2nm to 4nm. As an example, the diameter of the single-walled carbon nanotubes can be, but is not limited to, 0.2nm, 0.5nm, 1.5nm, 2.0nm, 2.5nm, 3.0nm, and 4.0nm.
[0064] As an embodiment, the dispersant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate, polyethylene oxide, polyether having multiple anchoring groups, polyethylene glycol and acrylonitrile multipolymer.
[0065] As one embodiment, the solvent is at least one of N,N-dimethylformamide, methanol, ethanol, ethylene glycol, ethyl acetate, acetone and deionized water.
[0066] As an embodiment, the stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 250 bar to 4000 bar. As an example, the operating pressure of the stripping machine can be, but is not limited to, 250 bar, 500 bar, 1000 bar, 1500 bar, 2000 bar, 2500 bar, 3000 bar, 3500 bar, 4000 bar.
[0067] As an implementation scheme, in step (III) of preparing the composite slurry, the grinding is performed by mechanical grinding, and the mechanical grinding is performed by high-speed shearing method to grind the particle size to less than 10 μm.
[0068] As one embodiment, the pre-dispersion liquid is mechanically ground before exfoliation.
[0069] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0070] Example 1
[0071] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0072] (I) Preparation of carbon-based precursors
[0073] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0074] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0075] (II) Preparation of porous carbon
[0076] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0077] (III) Preparation of composite slurry
[0078] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0079] Example 2
[0080] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0081] (I) Preparation of carbon-based precursors
[0082] 25.2 kg of coal tar (softening point of 280 ° C, coking value of 60%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0083] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0084] (II) Preparation of porous carbon
[0085] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0086] (III) Preparation of composite slurry
[0087] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0088] Example 3
[0089] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0090] (I) Preparation of carbon-based precursors
[0091] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of dopamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0092] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0093] (II) Preparation of porous carbon
[0094] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0095] (III) Preparation of composite slurry
[0096] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0097] Example 4
[0098] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0099] (I) Preparation of carbon-based precursors
[0100] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of magnesium oxide, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0101] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0102] (II) Preparation of porous carbon
[0103] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0104] (III) Preparation of composite slurry
[0105] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0106] Example 5
[0107] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0108] (I) Preparation of carbon-based precursors
[0109] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0110] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0111] (II) Preparation of porous carbon
[0112] The carbon-based precursor was soaked in 2M nitric acid for 25 hours, ultrasonicated for 10 hours, and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours, and passed through a 325-mesh sieve to obtain porous carbon.
[0113] (III) Preparation of composite slurry
[0114] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0115] Example 6
[0116] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0117] (I) Preparation of carbon-based precursors
[0118] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0119] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0120] (II) Preparation of porous carbon
[0121] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0122] (III) Preparation of composite slurry
[0123] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon and graphene quantum dots are added to obtain a pre-dispersion. The pre-dispersion is subjected to the first mechanical grinding, exfoliation and the second mechanical grinding in sequence. The pre-dispersion contains 20wt.% of porous carbon, 0.1wt.% of graphene quantum dots, 7wt.% of polyethylene glycol and the remainder of ethanol. Exfoliation is performed by a stripping machine, and the operating pressure of the stripping machine is 1000 bar. Mechanical grinding is performed by high-speed shearing method to grind the particle size to less than 10μm.
[0124] Example 7
[0125] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0126] (I) Preparation of carbon-based precursors
[0127] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0128] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0129] (II) Preparation of porous carbon
[0130] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0131] (III) Preparation of composite slurry
[0132] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon and conductive carbon black are added to obtain a pre-dispersion. The pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. The pre-dispersion contains 20wt.% porous carbon, 0.1wt.% conductive carbon black, 7wt.% polyethylene glycol and the remainder ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000 bar. Mechanical grinding is performed by high-speed shearing method to grind the particle size to less than 10μm.
[0133] Example 8
[0134] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0135] (I) Preparation of carbon-based precursors
[0136] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0137] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0138] (II) Preparation of porous carbon
[0139] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0140] (III) Preparation of composite slurry
[0141] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon and single-walled carbon nanotubes (with a diameter of 1 nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, exfoliation and the second mechanical grinding in sequence. The pre-dispersion contains 20 wt.% of porous carbon, 0.1 wt.% of single-walled carbon nanotubes, 7 wt.% of polyethylene glycol, and the remainder is ethanol. Exfoliation is performed using an exfoliator, and the operating pressure of the exfoliator is 1000 bar. Mechanical grinding is performed by high-speed shearing to grind the particle size to less than 10 μm.
[0142] Example 9
[0143] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0144] (I) Preparation of carbon-based precursors
[0145] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0146] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0147] (II) Preparation of porous carbon
[0148] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0149] (III) Preparation of composite slurry
[0150] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon, graphene quantum dots and conductive carbon black are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, exfoliation and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.05wt.%, the conductive carbon black is 0.05wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. The exfoliation is performed by a stripping machine, and the operating pressure of the stripping machine is 1000bar. The mechanical grinding is to grind the particle size to less than 10μm by a high-speed shearing method.
[0151] Example 10
[0152] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0153] (I) Preparation of carbon-based precursors
[0154] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0155] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0156] (II) Preparation of porous carbon
[0157] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0158] (III) Preparation of composite slurry
[0159] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon, conductive carbon black and single-walled carbon nanotubes (with a diameter of 1 nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. The pre-dispersion contains 20 wt.% of porous carbon, 0.05 wt.% of conductive carbon black, 0.05 wt.% of single-walled carbon nanotubes, 7 wt.% of polyethylene glycol, and the remainder is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000 bar. Mechanical grinding is to grind the particle size to less than 10 μm using a high-speed shearing method.
[0160] Embodiment 11
[0161] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0162] (I) Preparation of carbon-based precursors
[0163] 40.5 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 20.1 kg of KOH, 5.6 kg of melamine and 7.5 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of argon, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0164] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0165] (II) Preparation of porous carbon
[0166] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0167] (III) Preparation of composite slurry
[0168] Sodium dodecyl sulfate is dispersed in deionized water to obtain a dispersion, and porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 2nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 15wt.%, the graphene quantum dots are 0.01wt.%, the conductive carbon black is 0.1wt.%, the single-walled carbon nanotube is 0.04wt.%, the polyethylene glycol is 9wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0169] Example 12
[0170] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0171] (I) Preparation of carbon-based precursors
[0172] 25.2 kg of liquid asphalt (softening point of 280°C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 20 hours, mixed in a VC100 mixer at a speed of 250 r / min for 150 minutes, loaded into a carbonization crucible, and then placed in a rotary furnace for carbonization. Under the flow of 10 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0173] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 2.0°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 2.5°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.5°C / min; (4) Fourth heating step: keep at 900°C for 120 min.
[0174] (II) Preparation of porous carbon
[0175] The carbon-based precursor was soaked in 1M hydrochloric acid for 35 hours, ultrasonicated for 8 hours and washed 10 times with deionized water until neutral, then filtered and dried in a dryer at 100°C for 12 hours, ground with a ball mill for 13 hours, and passed through a 325-mesh sieve to obtain porous carbon.
[0176] (III) Preparation of composite slurry
[0177] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 2000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0178] Comparative Example 1
[0179] This embodiment is a method for preparing a nitrogen-doped conductive material, which includes the following steps.
[0180] (I) Preparation of carbon-based precursors
[0181] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH, 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0182] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0183] (II) Preparation of porous carbon
[0184] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0185] (III) Preparation of composite slurry
[0186] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and porous carbon is added to the mixture to obtain a pre-dispersion. The pre-dispersion is subjected to the first mechanical grinding, exfoliation and the second mechanical grinding in sequence. The porous carbon in the pre-dispersion is 20wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. The exfoliation is performed by a stripping machine, and the operating pressure of the stripping machine is 1000bar. The mechanical grinding is to grind the particle size to less than 10μm by a high-speed shearing method.
[0187] Comparative Example 2
[0188] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0189] (I) Preparation of carbon-based precursors
[0190] 25.2 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 12.6 kg of KOH and 2.2 kg of melamine were ground by a ball mill for 15 hours, mixed by a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0191] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0192] (II) Pickling
[0193] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground in a ball mill for 15 hours and sieved through a 325-mesh sieve to obtain the carbon material.
[0194] (III) Preparation of composite slurry
[0195] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then carbon material, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the carbon material in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0196] Comparative Example 3
[0197] This embodiment is a method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, which includes the following steps.
[0198] (I) Preparation of carbon-based precursors
[0199] 37.8 kg of liquid asphalt (softening point of 280 ° C, coking value of 70%), 2.2 kg of melamine and 6.2 g of nano-alumina were ground in a ball mill for 15 hours, mixed in a VC100 mixer at a speed of 300 r / min for 100 minutes, loaded into a carbonization crucible, and then placed in a roller kiln for carbonization. Under the flow of 5 L / min of nitrogen, the reaction was carried out according to the following heating method to obtain a carbonized product.
[0200] Heating method: (1) First heating step: room temperature rises to 300°C, heating rate is 3°C / min; (2) Second heating step: temperature rises to 480°C, heating rate is 1.25°C / min; (3) Third heating step: temperature rises to 850°C, heating rate is 2.06°C / min; (4) Fourth heating step: keep at 850°C for 180 min.
[0201] (II) Preparation of porous carbon
[0202] The carbon-based precursor was soaked in 1M hydrochloric acid for 30 hours, ultrasonicated for 10 hours and washed repeatedly with deionized water 10 times until neutral, then filtered and dried in a dryer at 100°C for 10 hours, ground with a ball mill for 15 hours and passed through a 325-mesh sieve to obtain porous carbon.
[0203] (III) Preparation of composite slurry
[0204] Polyethylene glycol is dispersed in ethanol to obtain a dispersion, and then porous carbon, graphene quantum dots, conductive carbon black and single-walled carbon nanotubes (diameter 1nm) are added to mix to obtain a pre-dispersion, and the pre-dispersion is subjected to the first mechanical grinding, stripping and the second mechanical grinding in sequence. Among them, the porous carbon in the pre-dispersion is 20wt.%, the graphene quantum dots are 0.02wt.%, the conductive carbon black is 0.05wt.%, the single-walled carbon nanotubes are 0.03wt.%, the polyethylene glycol is 7wt.%, and the balance is ethanol. Stripping is performed using a stripping machine, and the operating pressure of the stripping machine is 1000bar. Mechanical grinding is to grind the particle size to less than 10μm using a high-speed shearing method.
[0205] The nitrogen-doped multi-carbon-based composite conductive pastes obtained in Examples 1 to 12 and Comparative Examples 2 to 3 were dried into particles and then subjected to resistivity testing, and the nitrogen-doped conductive material of Comparative Example 1 was subjected to resistivity testing, and the results are shown in Table 1. The nitrogen-doped multi-carbon-based composite conductive pastes obtained in Examples 1 to 12 and Comparative Examples 2 to 3 and the nitrogen-doped conductive material of Comparative Example 1 were used as negative electrode conductive agents to test the cycle performance of silicon-based negative electrode materials, respectively, and the test conditions were as follows, and the test results are shown in Table 1. The same test as above was performed using Super-P as Comparative Example 4.
[0206] Cycle performance test: Silicon-based negative electrode material (carbon-coated SiO) and graphite were mixed in a mass ratio of 1:9 as negative electrode active material, mixed with a water dispersion of a binder acrylonitrile multi-polymer (LA132, solid content 15%) and a conductive agent in a mass ratio of 70:10:20 (wherein the conductive agent is the nitrogen-doped multi-carbon-based composite conductive slurry obtained in Examples 1 to 12 and Comparative Examples 2 to 3, or the nitrogen-doped conductive material of Comparative Example 1, or Super-P of Comparative Example 3), and an appropriate amount of water was added as a solvent to prepare a slurry, which was coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. Metal lithium was used as the counter electrode, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v) were used to form an electrolyte, and a polypropylene microporous membrane was used as a diaphragm to assemble a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of button cells was conducted on the battery test system of Wuhan Blue Electric Electronics Co., Ltd. Under normal temperature conditions, 0.1C constant current charge and discharge, charge and discharge voltage limited to 0.005-1.5V, 50-week capacity retention rate is the ratio of the charge capacity in the 50th week to the charge capacity in the first week. The 100-week capacity retention rate is the ratio of the charge capacity in the 100th week to the charge capacity in the first week.
[0207] Table 1 Physical properties and electrochemical properties of graphite-based negative electrode materials obtained in each group of examples
[0208] Example Resistivity(Ω / cm) First coulombic efficiency (%) 500-week capacity retention rate (%) Example 1 15.6 80.1 90.5 Example 2 21.7 78.5 89.3 Example 3 25.4 77.2 88.4 Example 4 24.1 77.8 88.8 Example 5 17.4 79.5 90.2 Example 6 11.2 77.8 87.1 Example 7 29.5 76.2 85.5 Example 8 10.8 77.8 85.7 Example 9 12.8 78.8 88.9 Example 10 13.8 79.2 89.1 Embodiment 11 19.5 78.5 88.2 Example 12 22.5 80.0 88.5 Comparative Example 1 40.2 75.6 86.5 Comparative Example 2 31.5 77.2 87.8 Comparative Example 3 33.1 76.8 87.2 Comparative Example 4 65.4 73.4 81.2
[0209] From the results in Table 1, it can be seen that compared with Comparative Examples 1 to 4, the nitrogen-doped multi-carbon-based composite conductive pastes prepared in Examples 1 to 12 have lower resistivity, and can be used as negative electrode conductive agents to improve the cycle performance of silicon-based negative electrodes. This is because the nitrogen-doped multi-carbon-based composite conductive paste of the present invention can form porous carbon by activation and pickling during preparation. After the porous carbon and the carbon-based conductive auxiliary material are composited, it has higher conductivity and can effectively separate Si particles from each other, thereby inhibiting their aggregation, and can also prevent the internal silicon from being unable to participate in charging and discharging when the aggregate becomes too large, thereby improving the electrochemical performance of the silicon-based negative electrode.
[0210] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nitrogen-doped multi-carbon-based composite conductive paste, characterized in that: Includes steps: (I) Preparation of carbon-based precursors The carbon material, an activator, a nitrogen source and nano-alumina are ground and mixed, and then carbonized under an inert atmosphere to obtain a carbon-based precursor, wherein the activator is a particle having oxygen-containing groups on the surface, the carbon material includes at least one of solid asphalt, liquid asphalt, coal tar, resin and aromatic oil, the activator is at least one of potassium hydroxide, sodium hydroxide, calcium carbonate and magnesium oxide, the nitrogen source is at least one of melamine, urea, dopamine and pyridine, and the carbonization temperature is increased by gradient, and the maximum temperature is increased to 800° C. to 900° C.; (II) Preparation of porous carbon The carbon-based precursor is acid-washed and then post-treated to obtain porous carbon; (III) Preparation of composite slurry The porous carbon and the carbon-based conductive auxiliary material are added to the dispersion to obtain a pre-dispersion solution, and the pre-dispersion solution is stripped and ground.
2. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 1, characterized in that: The invention comprises at least one of the following features (1) to (12): (1) The coking value of the carbon material is 10% to 80%; (2) The mass ratio of the carbon material, the activator, the nitrogen source and the nano-alumina is 14.0-62.0:11.5-32.5:0.5-10.0:5.0-10.0; (3) The grinding equipment used in step (I) of preparing the carbon-based precursor is a ball mill, and the ball milling time is 8 to 20 hours; (4) The mixing equipment used in step (I) for preparing the carbon-based precursor is a fusion machine or a VC mixer, and the mixing time is 60 min to 180 min; (5) The flow rate of the inert atmosphere is 0.5 L / min to 20.0 L / min; (6) The inert atmosphere comprises at least one of nitrogen, argon and helium; (7) The equipment used for carbonization is a roller kiln, a rotary kiln, a box furnace or a vertical kettle; (8) The solution used for pickling is hydrochloric acid, nitric acid or hydrofluoric acid; (9) The carbon-based conductive auxiliary material includes at least one of graphene quantum dots, conductive carbon black and single-walled carbon nanotubes; (10) The stripping is performed by a stripping machine, and the operating pressure of the stripping machine is 250 bar to 4000 bar; (11) In step (III) of preparing the composite slurry, the grinding is performed by mechanical grinding, wherein the mechanical grinding is performed by high-speed shearing method to grind the particle size to less than 10 μm; (12) The pre-dispersion liquid is mechanically ground before the stripping.
3. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 1, characterized in that: The heating rate of the carbonization is 1°C / min to 5°C / min.
4. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 1, characterized in that: The carbonization temperature is first raised to 250° C. to 300° C., then raised to 300° C. to 480° C., and then to 480° C. to 850° C., and then kept warm for 120 min to 300 min.
5. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 1, characterized in that: The post-treatment includes sequentially washing, filtering, drying, grinding and screening the acid-washed carbon-based precursor.
6. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 1, characterized in that: The pre-dispersion liquid includes 10wt.% to 25wt.% of porous carbon, 0.01wt.% to 2wt.% of carbon-based conductive auxiliary material, 5wt.% to 10wt.% of dispersant and 70wt.% to 90wt.% of solvent.
7. The method for preparing the nitrogen-doped multi-carbon-based composite conductive paste according to claim 6, characterized in that: Includes at least one of the following features ① to ④: ① The carbon-based conductive auxiliary material includes at least one of graphene quantum dots, conductive carbon black and single-walled carbon nanotubes; ② The carbon-based conductive auxiliary material at least includes single-walled carbon nanotubes, and the diameter of the single-walled carbon nanotubes is 0.2nm to 4nm; ③ The dispersant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate, polyethylene oxide, polyether with multiple anchoring groups, polyethylene glycol and acrylonitrile multipolymer; ④ The solvent is at least one of N,N-dimethylformamide, methanol, ethanol, ethylene glycol, ethyl acetate, acetone and deionized water.
8. A negative electrode sheet, comprising a negative electrode active material, a conductive agent and a binder, characterized in that: The negative electrode active material at least includes a silicon-based material, and the conductive agent includes a nitrogen-doped multi-carbon-based composite conductive paste prepared by the method for preparing a nitrogen-doped multi-carbon-based composite conductive paste according to any one of claims 1 to 7.
9. A secondary battery comprising a positive electrode and a negative electrode, characterized in that: The positive electrode includes a positive electrode conductor, the negative electrode includes a negative electrode conductor, and at least one of the positive electrode conductor and the negative electrode conductor includes a nitrogen-doped multi-carbon-based composite conductive paste prepared by the method for preparing a nitrogen-doped multi-carbon-based composite conductive paste according to any one of claims 1 to 7.
Citation Information
Patent Citations
Modified waste asphalt-based nitrogen-doped mesoporous carbon material as well as preparation method and application thereof
CN114604849A
Method for preparing silicon-carbon negative electrode material from photovoltaic waste silicon powder and graphene oxide
CN114975962A